2007
DOI: 10.1007/s11238-006-9015-1
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity Aversion in the Field of Insurance: Insurers’ Attitude to Imprecise and Conflicting Probability Estimates

Abstract: ABSTRACT. This article presents the results of a survey designed to test, with economically sophisticated participants, Ellsberg's ambiguity aversion hypothesis, and Smithson's conflict aversion hypothesis. Based on an original sample of 78 professional actuaries (all members of the French Institute of Actuaries), this article provides empirical evidence that ambiguity (i.e. uncertainty about the probability) affect insurers' decision on pricing insurance. It first reveals that premiums are significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 31 publications
5
69
0
5
Order By: Relevance
“…Ellsberg (1961) suggested that people often prefer to bet on risky prospects instead of ambiguous prospects, even if expected utility theory implies indifference. Confirming Ellsberg's conjecture, ambiguity aversion has been found in many empirical studies, including under market conditions and with monetary incentives (Cabantous 2007;Halevy 2007;Muthukrishnan et al 2009;Sarin and Weber 1993).…”
supporting
confidence: 60%
“…Ellsberg (1961) suggested that people often prefer to bet on risky prospects instead of ambiguous prospects, even if expected utility theory implies indifference. Confirming Ellsberg's conjecture, ambiguity aversion has been found in many empirical studies, including under market conditions and with monetary incentives (Cabantous 2007;Halevy 2007;Muthukrishnan et al 2009;Sarin and Weber 1993).…”
supporting
confidence: 60%
“…The second step consists in an aggregation of these evaluations through a multiple weights model. Such a model is compatible with the evidence found by Smithson (1999) and Cabantous (2007). More precisely, a decision maker will satisfy the conflict aversion hypothesis whenever her degree of conflict aversion is higher than her degree of imprecision aversion.…”
Section: Introductionsupporting
confidence: 77%
“…When there are only two states and ϕ is symmetric, the classical procedure and our approach are equivalent iff the decision maker degree of uncertainty aversion is larger than her degree of conflict aversion. Note that in these situations, the conflict aversion hypothesis described and observed by Smithson (1999) and Cabantous (2007) will not be satisfied. (i) For all P, Q ∈ P, there exists R ∈ P such that Π ⊗ (ϕ(P ), ϕ(Q)) = ϕ(R);…”
Section: ω}mentioning
confidence: 95%
See 1 more Smart Citation
“…np. Cabantous, 2007; podobną ideę na gruncie metodologicznym zaprezentowano w pracy: Domurat, 2011). …”
Section: Niejasność Wynikowa I Probabilistycznaunclassified